Effectiveness of Ethanolic Propolis Extract (EPE) Administration in Ameliorating Diabetic Mice Model - Muhaimin Rifa’i (Journal of Global Pharma Technology, 2017)
Diabetes mellitus (DM) is a group of metabolic disorder characterized by hyperglycemia resulting from defects in insulin action, insulin secretion, or both. Many efforts have been made to overcome this disease but until now has not been fully successful. This study aimed at examining CD34+, TER119+VLA4+, B220+  cell population,  and stromal cell-derived factor 1 (SDF-1) expression in an attempt to correct homeostasis indiabetic mice model with active disease.Three different EPE doses were tested (50, 100, and 200 mg/kg BW).  The oral administration of EPE was conducted for 14 days. On day 15, the bone marrow cells were isolated and then subjected to flow cytometry analysis, and data was processed by One-way ANOVA (p < 0.05) and Tukey test using SPSS 16.0 for Windows. The results showed that administration of EPE with the doses of 50 and 100 mg/kg BW) potentially increased cell proliferation. In contrast, the doses of 200 mg/kg BW seem to be in potentially suppressing cell proliferation. Taken together, propolis, which is involved in the induction of proliferation, show a rather in low doses, while high dose will give a suppression effect on cell proliferation and differentiation. Therefore, the use of propolis for treatment should consider the appropriate dose.  Keywords: B220, CD34, Diabetes mellitus, SDF-1, TER-119+VLA-4+.